Transforming workplace English in distance education: Exploring e-learning preferences and experiences in the digital age - Suliman, Zuleika; Sevnarayan, Kershnee (Journal of Research on English and Language Learning (J-REaLL), 2024)
In transforming digital progression in professional contexts, effective communication and career growth hinge significantly on mastering workplace English. Despite the increasing reliance on e-learning tools as a promising alternative in higher education, there exists a dearth of research focusing on individual preferences and experiences, particularly within distance education. This article fills this gap by conducting qualitative research firmly rooted in the community of inquiry theory. The primary objective of this study is to scrutinize the efficacy of e-learning tools and highlight factors that influence the preferences of first-year students engaged in distance education. Some key considerations encompass flexibility, interactivity, personalized learning, and accessibility. The research methodology involves observation of various e-learning platforms, in-depth interviews, and open-ended evaluation questions with first-year students who speak English as a second language in a South African open-distance e-learning university. The findings highlight an inclination towards virtual classrooms and customized online modules. Noteworthy aspects highlighted by participants include the significance of collaborative learning, real-world scenarios, continuous feedback mechanisms, and the integration of adaptive technologies. The significance of this research lies in its contribution to the advancement of distance education, which specifically focuses on workplace English skills. This research expands on distance education and provides specific implications for enhancing e-learning practices and their pivotal role in guiding the future workforce.